Unexpected acute pulmonary embolism in an old COVID-19 patient with warfarin overdose: a case report. Issue 6 (5th June 2021) - Coutrot, Maxime; Delrue, Maxime; Joly, Bérangère S; Siguret, Virginie
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 disease is strongly associated with a high incidence of thrombotic events. Anticoagulation could be a cornerstone in successfully managing severe forms of coronavirus disease 2019 (COVID-19). However, optimal anticoagulant dosing in elderly patients is challenging because of high risk of both thrombosis and bleeding. Case summary: We present here the case of an 89-year-old patient receiving warfarin for atrial fibrillation and valvular heart disease, admitted to the intensive care unit for respiratory failure due to COVID-19. The patient presented with a severe epistaxis associated with warfarin overdose [international normalized ratio (INR) > 10]. After a successful initial reversal using vitamin K per os, INR values greatly fluctuated up to 10, requiring repeated administrations of vitamin K. Despite starting low-molecular-weight heparin therapy at therapeutic dose as soon as INR value was below 2.0, the patient further developed an acute bilateral and proximal pulmonary embolism concomitantly with a sharp D-dimer increase. The combination of azithromycin intake, a known inhibitor of CYP2C9, with the presence of CYP2C9*2 and −1639G>A VKORC1, two variants associated with warfarin hypersensitivity, have likely contributed to explain the warfarin overdose and the difficulty to reverse warfarin effect in this patient. Discussion: This case report illustrates the complexity of COVID-19 pathophysiology and its management for physicians, especially in patients receiving vitamin K antagonists (VKAs). Infection, concurrent medication use, and pharmacogenetic factors involved in VKA metabolism and pharmacodynamics may lead to a loss of control of anticoagulation. Pulmonary embolism should still be considered in COVID-19 patients even with effective or overdosed anticoagulant therapy.